Enhacing Critical Thinking Skills through STEM-PjBL: A Quasi-Experimental Study on Temperature and Heat - Hadiatul Martini; Baiq Aryani Novianti; Khaerus Syahidi (Journal of Educational Studies, 2026)
Critical thinking ability is one of the essential skills that need to be developed in physics learning in the 21st century. However, students' critical thinking ability has not yet developed optimally, so a learning model that can actively involve students in problem solving is needed. One alternative that can be applied is the STEM–PjBL learning model. This study aims to analyze the effect of the STEM–PjBL learning model on students' critical thinking ability on temperature and heat material. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of 42 students of grade XI MA Tohir Yasin who were selected using a purposive sampling technique. Data were collected using a valid and reliable essay test, then analyzed using descriptive statistics and the Mann–Whitney U test. The results showed that the average posttest score of the experimental class (79.77) was higher than that of the control class (68.75), with a significance value of 0.005 (p < 0.05). Thus, the application of the STEM–PjBL learning model has a significant effect on students' critical thinking skills on temperature and heat material and can be an alternative physics learning method to develop critical thinking skills.